Difference in Left Ventricular Mass Index Between Hypertensive Patients With and Without Renal Artery Stenosis by Propensity Score Analysis. Issue 8 (14th July 2014) - Hoshida, Shiro; Shinoda, Yukinori; Inui, Hirooki; Hosoi, Ryoji; Teranishi, Fumiko; Asaoka, Nobuaki; Sugitani, Toshifumi; Hamasaki, Toshimitsu
<x xml:space="preserve">Abstract</x> This study aimed to define the difference in cardiac hypertrophy between hypertensive patients with and without renal artery stenosis (RAS). When cardiac ultrasonographic examination was performed in 971 consecutive hypertensive outpatients, renal peak systolic velocity (PSV) was examined. Compared with patients without RAS, those with RAS (PSV ≥180 cm/s, 4.1%) were significantly older and included a higher proportion of male patients and had a higher left ventricular mass index (LVMI). A stratified analysis in the selected 120 patients showed that the LVMI was significantly higher in patients with RAS than in those without RAS for each confounding factor such as age and blood pressure. RAS was independently associated with a higher LVMI on propensity score analysis and multivariate analysis. Thus, the difference in LVMI between hypertensive patients with and without RAS was confirmed, irrespective of age and blood pressure, by stratified propensity score analysis and multivariate regression analysis.